Vesicular fractions of sunflower apoplastic fluids are associated with potential exosome marker proteins - Regente, Mariana Clelia (2009)
Based on the presence of phospholipids in the extracellular fluids (EFs) of sunflower seeds, we have hypothesized on the existence of vesicles in the apoplastic compartment of plants. Ultracentrifugation of sunflower EF allowed the isolation of particles of 50-200 nm with apparent membrane organization. A small GTPase Rab was putatively identified in this vesicular fraction. Since Rab proteins are involved in vesicular traffic and their presence in exosomes from animal fluids has been demonstrated, evidence presented here supports the existence of exosome-like vesicles in apoplastic fluids of sunflower. Their putative contribution to intercellular communication in plants is discussed.